2011 IEEE Third International Workshop on Software Aging and Rejuvenation 2011
DOI: 10.1109/wosar.2011.15
|View full text |Cite
|
Sign up to set email alerts
|

Software Aging and Rejuvenation: Where We Are and Where We Are Going

Abstract: After 16 years, a significant body of knowledge has been established in the area of Software Aging and Rejuvenation (SAR). In this paper, we survey papers about SAR that appeared in IEEE conferences and journals, identify where SAR research has been mostly focused, and highlight some aspects deserving more attention, with the aim to provoke a constructive discussion among SAR researches about where SAR has arrived and where it should be headed in the next future.• the type of analysis that has been conducted, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 64 publications
0
31
0
Order By: Relevance
“…It is a known fact that a system maintainer can mess up perfectly fine functioning software through changing codes or inserting incorrect codes which is known as "ignorant injection" [8]. To provide a focus view of research areas on software aging Cotroneo et al [9] have analyzed more than 70 papers in which they have concluded that overall there are two major categories of research into understanding software aging the first is model-based analysis and the second is measurement-based analysis. Several measureable techniques have been proposed to detect software aging such as "aging indicators" and "time series analysis."…”
Section: A Software Agingmentioning
confidence: 99%
“…It is a known fact that a system maintainer can mess up perfectly fine functioning software through changing codes or inserting incorrect codes which is known as "ignorant injection" [8]. To provide a focus view of research areas on software aging Cotroneo et al [9] have analyzed more than 70 papers in which they have concluded that overall there are two major categories of research into understanding software aging the first is model-based analysis and the second is measurement-based analysis. Several measureable techniques have been proposed to detect software aging such as "aging indicators" and "time series analysis."…”
Section: A Software Agingmentioning
confidence: 99%
“…Although software rejuvenation can potentially mitigate integer overflow problems, its adoption is limited by the lack of an aging indicator, that is, a quantity that can be measured and that can be related to software aging phenomena of this kind [3], [6]. In the case of software aging phenomena that cause resource consumption or performance degradation, the amount of free resources or the average system response time are usually adopted as aging indicators, in order to forecast the occurrence of aging-related failures (e.g., by using time series and statistical data analysis) and plan software rejuvenation before the failure [8], [10].…”
Section: Monitoring For Integer Overflowsmentioning
confidence: 99%
“…Among software aging issues analyzed in the literature, most of previous studies have dealt with the consumption of memory and other OS resources, and with degradation of response time [6]. Indeed, these issues are the most frequent manifestations of aging-related bugs, as showed by empirical studies [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Software aging is the situation in which the accumulation of errors occurring in operational software system that has run for a long time that may lead to performance degradation, resource depletion and eventually causing the software to crash or hang [1]. David Parnas divided software aging into two categories: 1) the failure of the software to adapt with environment that is dynamic and 2) the result of the changes itself [2].…”
Section: Introductionmentioning
confidence: 99%